REAL-TIME UNDERWATER VISIBLE LIGHT COMMUNICATION USING PULSE WIDTH MODULATION AND LIGHT DEPENDENT RESISTORS - Ali Sher; Muhammad Izhar; Ilyas Khan; Subhi Mahmood Fadhl Hussein; Wasim Habib; Bilal Ur Rehman; Humayun Shahid; Muhammad Kashif Khan (Spectrum of Engineering Sciences, 2025)
Visible Light Communication (VLC) has emerged as a groundbreaking technology, utilizing light as a medium for wireless data transmission. This paper introduces an innovative Underwater Visible Light Communication (UVLC) approach for real-time imaging transmission. The proposed system employs Pulse Width Modulation (PWM) and an integrated Light Dependent Resistor (LDR) to achieve fundamental light detection capabilities. Our system can transmit data at 160 bits per second (bps) over substantial distances underwater, utilizing Light Emitting Diodes (LEDs) as optical transceivers. This setup ensures robust and efficient communication in aquatic environments and demonstrates visible LEDs' dual functionality for illumination and optical communication.